Influence of Mg2+ substitution on the magnetic and electrical properties of Li-Zn ferrite thick films synthesized with PVA matrix - Rendale, M. K.; Kulkarni, S. D.; Kulkarni, D. C.; Puri, Vijaya (Microelectronics International, 2011)
Purpose - The purpose of this paper is to investigate the effect of Mg2+ substitution on the magnetic and electrical properties of Li0.35-x Mg-2x Zn-0.3 Fe2.35-xO4 thick films synthesized with polyvinyl alcohol (PVA) matrix. Design/methodology/approach - The nanoferrites Li0.35-x Mg-2x Zn-0.3 Fe2.35-xO4 (x = 0, 0.07, 0.14, 0.21, 0.28 and 0.35) were synthesized by chemical technique using aqueous solution of PVA (the matrix) and thick films were fabricated by screen printing technique. The DC magnetic hysteresis measurements, AC magnetic susceptibility and DC electrical resistivity were measured as a function of temperature. Findings - The lattice parameter of thick film Li0.35-x Mg-2x Zn-0.3 Fe2.35-xO4 (x = 0, 0.07, 0.14, 0.21, 0.28 and 0.35) increases with the substitution of Mg2+ ions for Li1+ and Fe3+. The surface morphology of the thick films showed the grain size increasing with Mg2+ substitution till x = 0.21 and then decreasing for the higher concentrations of magnesium. The magnetic moment n(B) (mu(B)) computed from the M-s obtained by extrapolation of the magnetization curve showed a gradual decrease with the composition till x = 0.21, beyond which a sudden decrease was observed. The resistivity of the films at room temperature had variation with composition x, similar to that of magnetic moment. The activation energies Delta E-F and Delta E-P were found to vary with composition x of the ferrite system. Originality/value - The paper reports, for the first time, the magnetic and electrical properties of fritless Li0.35-xMg2xZn0.3Fe2.35-xO4 thick films using PVA polymer matrix. Up to x = 0.21 (Mg2+), grain size increases and Curie temperature decreases beyond which reverse effect takes place.
Keywords: Alternating current; Direct current; Electrical properties; Films (states of matter); Magnetic moments